Rodzina imigrancka z perspektywy historycznej: doświadczenia polskich pionierów w Winnipeg, 1896-1919 - Albański, Łukasz (Karkonoska Państwowa Szkoła Wyższa, 2011)
This paper focuses on an early Polish family life in Winnipeg. The family often served as a mechanism to reduce a sense of dislocation and to facilitate immigrants' adaptation. The family was also the primary economic unit. The family relations were affected by gender. Both immigrant men and women found themselves reconsidering traditional roles. Somehow immigration tested their family roles in new ways.
Keywords: immigrants; family; history; migration; gender; adaptation; Canada